Partial preferential chromosome pairing is genotype dependent in tetraploid rose - Bourke, Peter M.; Arens, Paul; Voorrips, Roeland E.; Esselink, G. Danny; Koning‐Boucoiran, Carole F. S.; van't Westende, Wendy P. C.; Santos Leonardo, Tiago; Wissink, Patrick; Zheng, Chaozhi; Geest, Geert; Visser, Richard G. F.; Krens, Frans. A.; et al. (The Plant journal : for cell and molecular biology, 2017)
Summary It has long been recognised that polyploid species do not always neatly fall into the categories of auto‐ or allopolyploid, leading to the term ‘segmental allopolyploid’ to describe everything in between. The meiotic behaviour of such intermediate species is not fully understood, nor is there consensus as to how to model their inheritance patterns. In this study we used a tetraploid cut rose (Rosa hybrida) population, genotyped using the 68K WagRhSNP array, to construct an ultra‐high‐density linkage map of all homologous chromosomes using methods previously developed for autotetraploids. Using the predicted bivalent configurations in this population we quantified differences in pairing behaviour among and along homologous chromosomes, leading us to correct our estimates of recombination frequency to account for this behaviour. This resulted in the re‐mapping of 25 695 SNP markers across all homologues of the seven rose chromosomes, tailored to the pairing behaviour of each chromosome in each parent. We confirmed the inferred differences in pairing behaviour among chromosomes by examining repulsion‐phase linkage estimates, which also carry information about preferential pairing and recombination. Currently, the closest sequenced relative to rose is Fragaria vesca. Aligning the integrated ultra‐dense rose map with the strawberry genome sequence provided a detailed picture of the synteny, confirming overall co‐linearity but also revealing new genomic rearrangements. Our results suggest that pairing affinities may vary along chromosome arms, which broadens our current understanding of segmental allopolyploidy. Significance Statement In polyploid species, variable pairing affinities among homologous chromosomes have been theorised but rarely experimentally observed. In this study, we have uncovered evidence for partial preferential pairing (also termed segmental allopolyploidy) in a tetraploid rose population (Rosa hybrida), and in doing so, have developed a meiotically‐tailored ultra‐high density linkage map of this important genus, carrying 25 695 SNP markers.